2001
DOI: 10.1111/j.1745-3984.2001.tb01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Comparability in Computerized Adaptive Testing: Issues, Criteria and an Example

Abstract: When a computerized adaptive testing (CAT) version of a test co‐exists with its paper‐and‐pencil (P&P) version, it is important for scores from the CAT version to be comparable to scores from its P&P version. The CAT version may require multiple item pools for test security reasons, and CAT scores based on alternate pools also need to be comparable to each other. In this paper, we review research literature on CAT comparability issues and synthesize issues specific to these two settings. A framework of criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 46 publications
0
39
0
12
Order By: Relevance
“…Wang & Kolen (2001) illustrated that if a score of 18 on the ACT Assessment scale score is used as a cut score for collegiate sports eligibility by the NCAA, there were 71% of the examinees who had P&P scores of 18 or above while there were 68% of the examinees who got CAT scores of 18 or above. If the CAT scores were used due to the CAT reliability over the P&P test, then it would be only 3% fewer examinees in the CAT compared to the examinees who took the P&P tests that were eligible for collegiate sports.…”
Section: The Advantages and Disadvantages Of Cbtsmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang & Kolen (2001) illustrated that if a score of 18 on the ACT Assessment scale score is used as a cut score for collegiate sports eligibility by the NCAA, there were 71% of the examinees who had P&P scores of 18 or above while there were 68% of the examinees who got CAT scores of 18 or above. If the CAT scores were used due to the CAT reliability over the P&P test, then it would be only 3% fewer examinees in the CAT compared to the examinees who took the P&P tests that were eligible for collegiate sports.…”
Section: The Advantages and Disadvantages Of Cbtsmentioning
confidence: 99%
“…The findings indicated that cumulative scores distribution in computerized adaptive tests are quite similar to one another, but they differed from the paperand-pencil tests scale scores. Wang & Kolen (2001) assumed that the differences in scoring methods might influence the major difference in scale score distribution for both test versions. Gallagher, Bennett, Cahalan, & Rock (2002) examined a computerized Mathematical Expression (ME) using ANOVA to detect construct-irrelevant variance.…”
Section: Validity Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Diákonkénti bontásban a lineáris, illetve az adaptív tesztkörnyezetben történt képességszint-becslés során elkövetett hiba nagyságát összehasonlítva (Wang és Kolen, 2001;Wang, 2010) megállapítható, hogy a lineáris formátumú teszt alapján történt képességszint-becslés hibáinak nagysága diákszinten átlagosan nagyobb (t=-7,54, p<0,01; se_átlag=0,53), mint ugyanazon diákok adaptív tesztkörnyezetben történt képességszint-becslésének hibája (se_átlag=0,49). A hatás-mérték 0,78, vagyis jelentős az eltérés.…”
Section: Iii145 a Lineáris éS Az Adaptív Tesztelés Során Kinyert Munclassified